The SOX9-MMS22L Axis Promotes Oxaliplatin Resistance in Colorectal Cancer - Liu, Yiqiang; Wu, Hong; Luo, Tao; Luo, Qiyu; Meng, Ziyu; Shi, Ying; Li, Feifei; Liu, Mingxin; Peng, Xinhao; Liu, Junjie; Xu, Chuan; Tang, Weizhong (Frontiers in Molecular Biosciences, 2021)
Background Colorectal cancer (CRC) is estimated to be one of the most common cancers and the leading cause of cancer-related death worldwide. SOX9 is commonly overexpressed in CRC and participates in drug resistance. In addition, DNA damage repair confers resistance to anticancer drugs. However, the correlation between DNA damage repair and high SOX9 expression is still unclear. In this study, we aimed to investigate the function and the specific underlying mechanism of the SOX9-dependent DNA damage repair pathway in CRC. Methods The expression levels of SOX9 and MMS22L in CRC were examined by immunohistochemistry (IHC) and TCGA analysis. RNA sequencing was conducted in RKO SOX9-deficient cells and RKO shControl cells. Mechanistic studies were performed in CRC cells by modulating SOX9 and MMS22L expression, and we evaluated drug sensitivity and DNA damage repair signaling events. In addition, we investigated the effect of oxaliplatin in tumors with SOX9 overexpression and low expression of MMS22L in vivo. Results Our study showed that SOX9 has a higher expression level in CRC tissues than in normal tissues and predicts poor prognosis in CRC patients. Overexpression and knockdown of SOX9 were associated with the efficacy of oxaliplatin. In addition, SOX9 activity was enriched in the DNA damage repair pathway via regulation of MMS22L expression and participation in DNA double-strand break repair. SOX9 was upregulated and formed a complex with MMS22L, which promoted the nuclear translocation of MMS22L upon oxaliplatin treatment. Moreover, the xenograft assay results showed that oxaliplatin abrogated tumor growth from cells with MMS22L downregulation in mice. Conclusions In CRC, activation of the SOX9-MMS22L-dependent DNA damage pathway is a core pathway regulating oxaliplatin sensitivity. Targeting this pathway in oxaliplatin-resistant CRC cells is a promising therapeutic option.